JENIS-JENIS CAPUNG DI CAGAR ALAM TELUK KLOWE KECAMATAN ENGGANO KABUPATEN BENGKULU UTARA, PROVINSI BENGKULU - Helmiyetti, Helmiyetti; Siboro, Merliana Br; Tarantona, Mariska (Konservasi Hayati, 2019)
The purpose of this study is to find out the types of dragonflies (Odonata) found in the Klowe Bay Nature Reserve, Enggano sub-district, North Bengkulu Regency, Bengkulu Province. The study was conducted in the Klowe Bay Nature Reserve, Enggano sub-district, North Bengkulu Regency, Bengkulu Province in January 2018, which was identified in the Animal Physiology laboratory, Basic Science Biology, University of Bengkulu. by means of purposive sampling by surveying locations in accordance with dragonfly living conditions such as the presence of water and the presence of plants that are habitat for small insects that are food for dragonflies so that 2 points are determined. Dragonflies collected by exploring by swinging the net towards the dragonfly. The sample obtained is put into a killing bottle contains cotton in which the cotton has been given chloroform. The results obtained are 4 types of dragonflies with 15 individuals included in the Anisoptera sub-order. The types obtained include the Libellulidae Family, namely Orthetrum sabina, Pantala flavescens, Crocothemis Servilia, and Orthetrum glaucum.